Gestión de facturación en la Corporación Nacional de Electricidad CNEL EP Los Ríos - Garcia Santos, Verónica Patricia (2021)
The subject of this study is "Billing Management in the National Electricity Corporation CNEL EP Los Ríos", with the aim of analyzing and comparing the consumption in the invoices of the various users, this is carried out under the Financial Management research line , Administrative, Tax, Audit and Control and the sub-line Companies and Public and Private Institutions; While, the implemented methodology comprises the descriptive method that collects information through the interview technique and the interview guide instrument applied to the Leader of the Cadastre and Billing area of the CNEL-Los Ríos company, where the identified problem compromises the management of billing directly and it occurs because as a result of the health emergency experienced worldwide by Covid-19, meter readings were not made, data were not entered that allow billing real values and therefore various problems were generated within In the area, users filed complaints because, since there was no meter reading, values related to customer consumption were averaged and this generated great discomfort, resulting in increased difficulties and problems in the development of activities in the area. In conclusion, the implementation of a continuous and timely process for the management of meter reading and management in the billing area will allow claims to decrease in a way that generates user satisfaction.